Kemampuan Menggunakan Personalpronomen Bahasa Jerman - Mu'minin, Ainul; Al-Ilmullah, Syarifah Fathimah; Saud, Syukur (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This study aims to examine the ability of Class XI.4 students at SMA Negeri 4 Enrekang to use German Personalpronomen. A quantitative descriptive method was employed in this research. The population consisted of 61 students from Class XI, and a sample of 25 students from Class XI.4 was selected using random sampling techniques. The analysis results revealed that the students’ ability to use Personalpronomen was categorized as adequate, with an average score of 63.86%. This ability was influenced by internal factors, including physical conditions, fatigue, and psychological aspects, as well as external factors such as family support, school environment, and community influences. Keywords: Personalpronomen, Nomminativ, Akkusativ, Dativ, Deutsch